1985
DOI: 10.1902/jop.1985.56.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Freeze‐Dried Bone Allografts Combined with Tetracycline in the Treatment of Juvenile Periodontitis

Abstract: Sixteen patients diagnosed as having juvenile periodontitis were randomly placed into one of two treatment groups. Group I received local and systemic tetracycline (TTC), while Group II received no antibiotics. Osseous defects were grafted with allogeneic freeze-dried bone (FDBA) mixed with TTC powder (Group Ia) or FDBA alone (Group IIa). Contralateral defects were debrided only in both Groups (Ib and IIb). Direct reentry evaluation of 104 measurement sites demonstrated significantly greater bone fill (mean = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…Also, local administration of tetracycline (10 g/ mL) with freeze-dried bone allograft was effective in bone regeneration. [18][19][20] These release patterns could be optimized by examining the efficacy of tetracyclineloaded membranes for bone regeneration in vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, local administration of tetracycline (10 g/ mL) with freeze-dried bone allograft was effective in bone regeneration. [18][19][20] These release patterns could be optimized by examining the efficacy of tetracyclineloaded membranes for bone regeneration in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 Applications of membranes for GTR have been confined to the subgingival barrier functions; however, many studies have provided evidence that some drugs, including tetracycline, initially can promote the growth of periodontal ligament or alveolar bone in periodontal therapy. [18][19][20] Osseous regeneration in periodontal defects is increased by local administration of tetracycline due to its anti-collagenolytic effect, which enhances bone-forming ability via osteoblast cell chemotaxis and reduced bone resorption. [18][19][20] Therefore, controlled tetracycline delivery from barrier membranes may be highly beneficial for the treatment of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the percentages of motiles and the increase in the percentages of cocci were highly significant in the treatment groups compared with the control group. Fig.2 Rate of release ( ƒÊg/h) of DOXY and CHx from HPMC membranes Table 1 Summary of the statistical differences between all the groups at each visit for the measurement parameters determined by analysis of variance Table 2 Mean and standard deviation of pocket depth in the treatment and control groups at the baseline (Visit 0) and for each visit up to 10 w (Visit 4) Table 3 Mean and standard deviation of gingival shrinkage for the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) Table 4 Mean and standard deviation of the bleeding score for the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) Table 5 Mean and standard deviation of crevicular fluid flow in the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) Table 6 Mean and standard deviation of the percentage of curved and motile rods and spirochaetes in the treatment and control groups at the baseline (Visit 0) and at each visit up to 10 w (Visit 4) [24][25][26] and concentration in crevicular fluidi [11] , but also their fibroblast-stimulating activity [27,28] , enhancement of bone regeneration [29][30][31] , substantivity to mineralized tissues [32], and anticollagenolytic activity [33,34].…”
mentioning
confidence: 99%
“…Studies have shown that a combination of chemically-modified tetracyclines together with bisphosphonates, when delivered systemically, is synergistically effective in suppressing periodontal bone loss. 3 Regeneration of furcation defects in humans was documented with histologic studies when such defects were treated with an allograftalloplast-tetracycline composite graft combined with an absorbable membrane for GTR. 4 Periodontal plus AB is a collagen fibril based formulation containing tetracycline hydrochloride (2mg of tetracycline) in 25mg of collagen (Biocompatible Type 1 collagen) was used.…”
Section: Discussionmentioning
confidence: 99%